Improving soil chemical properties by NPK fertilizer application and residual rice husk biochar effect on irrigation paddy field - Diana Samira; . Sufardi; . Zaitun; . Chairunas; Anischan Gani (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
The research objective was to study effects of NPK fertilizer and biochar residue on soil chemical properties of paddy on second planting. Experiment was arranged in a randomized complete block design in a factorial design with four replications. Biochar consisted of two levels, i.e. without biochar residue and with biochar residue 10 ton ha-1. NPK fertilizer consisted of three levels, i.e. without NPK, NPK 60 kg ha-1, and NPK 120 kg ha-1. The result showed that application NPK fertilizer and biochar residue on second planting increase total N 22.22%, available P 12.18%, available K 17.50%, and organic C 56.69% compare than first planting